Animation as an aid to support the teaching of cyber security concepts. Issue 5 (3rd September 2018) - Taylor, Mark; Baskett, Mike; Allen, Mark; Francis, Hulya; Kifayat, Kashif
ABSTRACT: Animated learning materials have the potential to support the teaching and learning process. In this paper, we examine the comparative usefulness of animated and static learning materials for teaching cyber security concepts to a group of UK undergraduate computer science students. The animated cyber security learning materials appeared to be viewed by the undergraduate computer science participants overall as being slightly more informative than the equivalent static learning materials for learning some cyber security concepts.